TAVI versus SAVR in intermediate-risk patients with severe aortic stenosis and chronic kidney disease: a matched comparison in a subcohort from the GARY registry. (3rd October 2022) - Mas-Peiro, S; Faerber, G; Herrmann, E; Bauer, T; Bleiziffer, S; Bekeredjian, R; Boening, A; Frerker, C; Beckmann, A; Moellmann, H; Ensminger, S; Hamm, C; et al.
Abstract: Background: According to American and recent European guidelines, both transcatheter aortic valve implantation (TAVI) and surgical aortic valve replacement (SAVR) may be used to treat severe aortic stenosis in a subgroup of patients with intermediate surgical risk, in spite of slight differences in recommended age limits (ACC/AHA: 65–80 years and ESC/EACTS: <75 years). A shared therapeutic decision is made with the patient, based on a heart team assessment. For this, individual factors should be taken into account. Concomitant chronic kidney disease (CKD) is a prognostic factor in such patients, and CKD stage ≥3a and ≥3b has been shown to be a significant independent risk factor for SAVR and TAVI, respectively. Purpose: To compare TAVI vs. SAVR outcomes in a subgroup of patients for whom both therapies could possibly be considered according to current guidelines. Methods: The large nation-wide German Aortic Valve Registry (GARY) includes data from patients treated with TAVI or SAVR. A subcohort of patients from GARY with intermediate surgical risk (age ≤80 years, STS-score 4–8) and moderate-to-severe chronic kidney disease (CKD stages 3a, 3b, and 4) was selected. A matched analysis of 704 patients undergoing TAVI and 374 undergoing SAVR was carried out using a propensity score method. Primary endpoint was 1-year survival. Clinical complications and specifically the need for postprocedural new-onset dialysis were secondary endpoints. Results: TAVI and SAVR showed similar survival results at 1 year in a Kaplan-Meier analysis (HR [95% CI] for TAVI: 1.271 [0.795, 2.031], p=0.316). Despite a numerically higher post-procedural short-term survival in TAVI patients and a numerically higher 1-year survival in SAVR patients, such differences did not reach statistical significance (96.4% vs. 94.2%, p=0.199, and 86.2% vs. 81.2%, p=0.316, respectively). In weighted analyses, need for permanent pacemaker, vascular complications, and moderate-to-severe valvular regurgitation were significantly more common with TAVI, whereas patients undergoing SAVR had significantly higher rates of myocardial infarction, and transient ischaemic attack, needed more transfusions for bleeding, and had a significantly longer intensive care unit stay and overall hospital stay. The need for new-onset dialysis for a limited time was more common after SAVR (p<0.0001); however, very few patients required chronic dialysis either after TAVI or after SAVR. Conclusion: In a matched analysis of intermediate-risk patients with severe aortic stenosis and a concomitant moderate-to-severe CKD, for whom both TAVI and SAVR could possibly be considered, both approaches showed excellent and comparable results. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The registry receives financial support in the form of unrestricted grants by medical device companies (Edwards Lifesciences, JenaValve Technology, Medtronic, Sorin, St. Jude Medical, Symetis S.A.).In addition, there is unrestricted support by funding statisticians by the DZHK (Deutsches Zentrum für Herz-Kreislaufforschung).